(untitled) (Research, Society and Development, 2021)
Breast cancer is still a disease full of stigmas and presents several threatening situations for its victims, affecting their quality of life. There are cases in which cancer is at an advanced stage, requiring the use of mastectomy, a radical and, therefore, mutilating surgery, causing painful changes in women’s lives, such as changes in self-image, self-esteem and commitment of sexuality. To analyze the psychosocial repercussions for women after mastectomy. This is an integrative literature review, using as a basis for research Sciello, Medline and LILACS, published in the period 2015-2020, as inclusion criteria for research specifically dealing with the topic, in languages: English and Portuguese, excluding articles whose theme is not relevant to the research, or duplicate results. The data found were analyzed, compared and discussed. From the survey carried out on the 27 articles found in the Medline, Scielo and Lilacs database, 05 studies were excluded and for this research 22 studies were used, being 07 related to the first specific objective, 09 related to the second specific objective and 06 to the third specific objective of this research.